Booker T. Washington: His contribution to education for minority groups - Zhinin, Karina; Palaguachi, Miriam
Our thesis is about Booker T. Washington, one of the most important black leaders of the United States. We have divided the thesis in six chapters which contain the following: First of all, we wrote a biography of the author which contains his early life, adult life, his freedom, his time without Education, marriages and children and his struggle for an education. Second, we have presented the way he searched for an education. We have included an overview of his career; how his youth was passed and how he studied; to the Tuskegee Institute, such as the Tuskegee people, his early days at Tuskegee, teaching school in a stable, helping others and raising money. Third, we have included his influence on the American Educational System: on Politics, on Public speaking and on wealthy friends and benefactors. Finally, we have mentioned his legacy: the heritage he left for minority groups, his last words, and his laying down of his burden